El análisis de la política exterior - Tomassini, Luciano (Estudios Internacionales, 1988)
The present work aims to reveal some of the necessary elements to take into account in the analysis of foreign policy. We postulate the existence of a close link between the analysis of foreign policy, the planning or formulation of that policy, the quality of the information systems available to foreign services, the decision-making processes and, finally, the mechanisms used to implement those decisions. For the practical purposes that these pages pursue, the process of formulating the policy and its analysis tend to be identified, since the latter always constitutes the anticipation or the reflection of the former.